Perancangan Buku Ilustrasi Interaktif Sebagai Media Edukasi Energi Alternatif Bioenergi untuk Usia 7-12 Tahun - Sinaga, Anatasya Caroline Nauli; Kusumandyoko, Tri Cahyo (BARIK, 2023)
Currently, Indonesia has a large potential for bioenergy raw materials, but its utilization is still far from the target of the National Energy Policy in 2025 and 2050, so education is needed for the nation's next generation to meet the target and mitigate environmental damage. Although bioenergy has been accommodated in elementary school subjects, in fact educational media from schools and outside schools have never existed in Indonesia before. This study aims to provide education on alternative energy bioenergy as a substitute for conventional energy and environmentally friendly clean energy using interactive book media. This study used a qualitative method with Miles and Hubberman's data analysis techniques including data reduction, data display and conclusions drawing. In designing media, Eric Karjaluoto (2014) applies design methods with the Discovery, Planning, Creative, Application stages. Based on the results of testing on children aged 7-12 years, it is known that the design of interactive illustration books can increase children's understanding of alternative bioenergy by being interactive and having good visuals.